Multiple antibiotics loaded starch nanoparticles : a strategy to prevent wide range bacteria - Nor Syahida Ismail (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This report discuss about the antimicrobial study of pathogenic bacteria by the disinfection using antibiotic loaded starch nanoparticle. The soluble form of starch nanoparticle is used to be an advantage to encapsulate the antibiotics. The antibiotics used in this study include amphicilin, tetracycline, penicillin and streptomycin. These encapsulated antibiotics were introduced to different types of bacteria (Escherichia coli, Proteus mirabilis, and Streptococcus pyogenes) to study their inhibitory effect. The encapsulation of the antibiotic in starch nanoparticle was intended to be used as broad spectrum against pathogenic organisms. The preparation of starch loaded antibiotic was carried out using microemulsion nanoprecipitation methods which do not require extreme conditions, sophisticated equipment, and hazardous reagents. The starch is dissolved in alkaline urea solution and precipitated in ethanolic emulsion system which yields smaller sized nanoparticles with higher surface area thus increase the efficiency of low water soluble drug molecules loading. The nanoparticles obtained are not vulnerable to clumping. The morphological assessment of the starch nanoparticles was characterized by using Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM). The antimicrobial study was done using disk diffusion test with different concentration of starch nanoparticles loaded with antibiotics. The encapsulation of multiple antibiotics and their inhibition is an indicator to study the efficacy of the starch nanoparticles. This study in an indicator to improve the effectiveness of drugs capability and produced by cheap source of material that brought large impact.